Sensitive industries lenses: the effect of cash holdings and financial constraints on Corporate Social Responsibility performance in Latin America - Cunha, Lucelma Maria dos Santos (2024)
This study aims to enhance the understanding of how sensitive industries influence the level of corporate financial resources and the availability of external funds for sustainable practices. Specifically, it examines how industry sensitivity moderates the effect of cash holdings, financial constraints, and their combined effect on corporate social responsibility (CSR) performance. To test the hypotheses, we employ linear regression models using data from 256 publicly traded non-financial firms in Argentina, Brazil, Chile, Colombia, Mexico, and Peru, covering 1,416 firm-year observations from 2015 to 2022. Firms are classified as sensitive or non-sensitive based on their four-digit SIC codes. CSR performance is proxied by the overall Environmental, Social, and Governance (ESG) score from LSEG Workspace, while cash holdings are measured as cash and cash equivalents to total assets. Financial constraints are assessed using the SA Index. As a robustness check, we also consider cash and short-term investments and the KZ and WW indexes as alternative proxies for cash reserves and financial constraints. Additionally, the study evaluates the ESG pillars separately, conducts a temporal analysis by examining the effects of the variables on CSR in subsequent periods, and carefully accounts for potential endogeneity among the variables. The results reveal three key findings. First, industry sensitivity does not alter the positive relationship between cash reserves and CSR performance. Second, industry sensitivity can reduce the negative effect of financial constraints on CSR performance. Finally, firms with greater financial constraints that hold more cash demonstrate superior CSR performance, regardless of industry sensitivity. These findings underscore the importance of industry affiliation in assessing a company\'s sustainability performance, as sector-specific factors can significantly influence access to external financial resources for CSR initiatives. Furthermore, they highlight that, regardless of industry sensitivity, developing effective liquidity management strategies to meet stakeholder expectations is crucial for firms aiming to enhance their CSR engagement.